Growth of inclined fatigue cracks using the biaxial CJP model - G. Laboviciute; C. J. Christopher; M. N. James; E. A. Patterson (Fracture and Structural Integrity)
The CJP model of crack tip stresses is a modified version of the Williams crack tip stress field which takes account of simplified stress distributions that arise from the presence of a zone of plastic deformation associated with the crack flanks and crack tip, and that act on the elastic field responsible for driving crack growth. The elastic stress field responsible for crack growth is therefore controlled by the applied loading and by the induced boundary stresses at the interface with the plastic zone. This meso-scale model of crack tip stresses leads to a modified set of crack tip stress intensity factors that include the resultant influence of plastic wake-induced crack tip shielding, and which therefore have the potential to help resolve some longstanding controversies associated with plasticity-induced closure. A full-field approach has now been developed for stress using photoelasticity and also for displacement using digital image correlation. This paper considers the characterisation of crack growth rate data with the biaxial CJP model, using compact tension specimens that contain inclined cracks at the notch tip with initial angles of 30°, 45° and 60° to the horizontal axis. Significant experimental difficulties are experienced in growing cracks in a biaxial field under uniaxial tensile loading, as the natural tendency of the crack is to turn so that it becomes perpendicular to the maximum principal stress direction. However, crack angle is not an issue in the CJP model which calculates the stress field parallel with, and perpendicular to, the crack plane. These stress components can be rotated into directions comparable with the usual KI and KII directions and used to calculate stress intensity parameters that should be directly comparable with the standard stress intensity formulations. Another difficulty arises, however, in finding published expressions for KI and KII for CT specimens with curved or kinked cracks. The CJP model has been successful in achieving a sensible rationalisation of crack growth rate data for the specimens considered in this work, although some observations are not easily explained. Nonetheless, considering the complexity of characterising crack growth rates for cracks with an initial orientation of 30°, 45° or 60° to the horizontal and which subsequently change angle during growth, the results found so far indicate that there is value in further pursuing the CJP approach. The paper introduces future research directions for the CJP model.